Comparison of complications according to incision types in nipple-sparing mastectomy and immediate reconstruction. (October 2020) - Park, Soeun; Yoon, Changik; Bae, Soong June; Cha, Chihwan; Kim, Dooreh; Lee, Janghee; Ahn, Sung Gwe; Roh, Tai Suk; Kim, Young Seok; Jeong, Joon
Abstract: Background: Nipple-sparing mastectomy (NSM), followed by immediate reconstruction (IR) of the breast, has become a preferred surgical procedure with good cosmesis results and patient satisfaction. However, nipple-areolar complex (NAC) ischemia and necrosis remain major problems after NSM and IR. Methods: We retrospectively analyzed patients who underwent NSM and IR at Gangnam Severance Hospital from January 2009 to June 2018. We compared the patient characteristics and complication rate among three different incisions (inframammary fold [IMF], radial, periareolar). Additionally, we identified the risk factors of NAC necrosis. Results: Data from 290 eligible breasts in 275 patients were analyzed. Patients with IMF incision had relatively lower breast weights. The overall complication rate was the highest with periareolar incision and the lowest with IMF incision (42.6% vs. 18.8%, p < 0.001). The rate of NAC ischemia or necrosis was significantly different among the three incisions (9.7%, 17.0%, and 31.1% in IMF, radial, and periareolar, respectively; p < 0.001). Moreover, surgical treatments were more frequently needed in patients with periareolar incision. Periareolar incision, short distance from the tumor to the nipple base, and large breast weight were independent risk factors of NAC ischemia or necrosis in multivariable analysis. Conclusions: Compared with IMF incision, periareolar incision was associated with higher incidences of surgical complications and NAC necrosis. Careful consideration is needed when planning NSM in patients with a large breast volume or a tumor close to the nipple. Highlights: Periareolar incision shows higher complication rate in nipple-sparing mastectomy. Periareolar incision is a risk factor for nipple-areolar complex necrosis. Other risk factors include tumor-nipple distance and breast weight.